Comparison of Filtration Processes Using Microfiltration, Ultrafiltration, Nanofiltration and Reverse Osmosis Methods on The Characteristics of Lemon Juice Functional Beverages At Pilot Scale - yusep ikrawan; Jaka Rukmana; Thomas Gozaly; Rini Triani; Wildan Qoharisma Salam; Hari Hariadi (Politeknik Negeri Lampung., 2024)
This study aims to determine the comparison of filtration processes using filtration membranes which include Microfiltration, Ultrafiltration, Nanofiltration and Reverse Osmosis on the characteristics of lemon juice functional drinks on a pilot scale, so that the stability of product results from the four different methods can be known. The best product quality parameters in this study include vitamin C content, total acid content, total soluble solids content, antioxidant activity, pH value, viscosity value, *b value (yellowish color), total microbial reduction, and hedonic quality test (aroma, taste, and aftertaste). So that a comparison of product characteristics can be obtained. The research conducted will go through three stages including the manufacture of control juice products as a comparison, the characteristics of products processed using membrane filtration machines and data processing using t tests conducted to find a comparison of the results of these products.The results of this study are the manufacture of lemon juice functional beverages using the filtration membrane method affects the vitamin C content, total acid content, total dissolved solids and antioxidant activity because the pore size of the membrane will decrease and the particles contained in the sample will be increasingly filtered and after being compared between each method, the highest results are obtained in the microfiltration method and the lowest is reverse osmosis. The manufacture of lemon juice functional beverages using the filtration membrane method affects the pH value, viscosity and color because the pore size of the microfiltration membrane to reverse osmosis is getting smaller so that it will decrease the pH value, viscosity and color. The manufacture of lemon juice functional beverages using the filtration membrane method affects the quality of the product, where in organoleptic testing the color attributes of the MF method produce lemon yellow beverage products. At the aroma attribute, the UF method produces a typical lemon-scented beverage product. At the taste attribute, the RO method produces a very sour beverage product typical of lemon. At the aftertaste attribute, the MF method produces very bitter beverage products.